Influence of Astigmatism in Reflector Feeds - Tokan, Fikret (IEEE, 2016)
Dielectric lens antennas are extensively used in wideband millimeter wave applications in recent years, since they exhibit high gain and high radiation efficiency thanks to the dense dielectric materials in the lens core. The planar dielectric lens antennas have different phase center locations in E- and H-planes which is known as astigmatism problem. In this paper, an ultra-wideband planar dielectric lens antenna will be used as the feed of a reflector antenna and the influence of astigmatism effect on the radiation patterns of the reflector antenna will be deeply investigated.
Keywords: astigmatism; dielectric lens antenna; phase center; ultra wideband; Computer Science; Engineering; Telecommunications